THE EFFECTIVENESS OF ENGLISH SONGS IN TEACHING PRONUNCIATION TO ELEMENTARY SCHOOL STUDENTS IN SD BINTANG PERTIWI - Hermansyah Hermansyah; Cici Handayani; Dewi Wulandari (Universitas Islam Sumatera Utara (UISU), 2018)
The objective of this research is to find out the effectiveness of using English songs in teaching pronunciation to elementary students with descriptive method. Descriptive method was taken from the description of the situation of the object based on the fact in the field. Meanwhile, the research design which was conducted in this research was classroom action research design by Miles and Hubermann (2010). Based on the research result and discussion, the use of English songs as the media in teaching pronunciation to the students in SD Bintang Pertiwi, the students’ ability in pronouncing English words has improved significantly. Songs were used as media because the lyrics of the song were easy to memorize. Therefore, it is possible for the students to comprehend the words they have listened and pronounced. English songs are effective to use as media in teaching pronunciation to elementary students. There is a significant improvement of students’ ability in pronouncing English words.